2010
DOI: 10.1542/peds.2009-2693
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A and Related Compounds in Dental Materials

Abstract: CONTEXT Dental sealants and composite filling materials containing bisphenol A (BPA) derivatives are increasingly used in childhood dentistry. Evidence is accumulating that BPA and some BPA derivatives can pose health risks attributable to their endocrine-disrupting, estrogenic properties. OBJECTIVES To systematically compile and critically evaluate the literature characterizing BPA content of dental materials; to assess BPA exposures from dental materials and potential health risks; and to develop evidence-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
150
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(156 citation statements)
references
References 63 publications
(104 reference statements)
1
150
0
5
Order By: Relevance
“…Thus, on one hand, BPAfree resinous dental materials may be advantageous for avoiding potential toxic effects to the patients (25), but on the other hand. The absence of BPA may affect negatively the adhesion of materials to dental tissues (11). In previous studies, EWB showed better adaptation compared to conventional sealants (9,28).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Thus, on one hand, BPAfree resinous dental materials may be advantageous for avoiding potential toxic effects to the patients (25), but on the other hand. The absence of BPA may affect negatively the adhesion of materials to dental tissues (11). In previous studies, EWB showed better adaptation compared to conventional sealants (9,28).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, resin-based materials, although more and more popular like composite resins and pit and fissure sealants, have caused concern due to the presence of 2,2-bis(4-hydroxyphenyl)propane (Bisphenol A -BPA) (10). BPA is a plastic used in the fabrication of several other products, including bottles, baby bottles, detergents, food packing and its derivatives, may present hazard to health (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bisphenol A (BPA) is an environmental contaminant that is used in the manufacturing of epoxy resins (e.g., food packaging and can-coating), polycarbonate, and numerous plastic products [Vandenberg et al 2009;Fleisch et al 2010]. Approximately three million tons of BPA are produced annually and almost 100 tons of BPA enters into the environment each year [Vandenberg et al 2009].…”
Section: Introductionmentioning
confidence: 99%
“…Polycarbonate plastics are being utilized for making various articles including baby feeing bottles, sippers, cups, water bottles, microwave ovenware, storage containers, returnable water and milk bottles, and refillable water containers. Numerous studies have shed light on the migration of BPA from various polycarbonate and canned products into the food and drinks including feeding bottles (Brede et (Sungur et al, 2014) etc.Besides, the non-food sources have their equal contribution to the humanexposure which could be from dust (Fu and Kawamura, 2010), thermal paper (Liao and Kannan, 2011), dental materials (Fleisch et al, 2010) and medical devices (Calafat et al, 2009;Haishima et al, 2001). Due to its high volume production and widespread use in plastics and cans, there is pervasive environmental contamination and well predictable and chronic exposure of BPA towards people of all ages.…”
Section: Introduction:-mentioning
confidence: 99%